Vitamin C content in yogurt with the addition of Tawangmangu tangerine juice (Citrus nobilis var. Tawangmangu) - RIA NUR KHASANAH; TJAHJADI PURWOKO; ARI SUSILOWATI (Nusantara Bioscience, 2015)
Abstract. Khasanah RN, Purwoko Tj, Susilowati A. 2015. Vitamin C content in yogurt with the addition of Tawangmangu tangerine juice (Citrus nobilis var. Tawangmangu). Nusantara Bioscience 7:  149-152. Yogurt is fermented milk that has an acid taste and known as probiotic food product that gives extra nutritional value. Most consumers like yogurt with fruit flavor added, one of them is orange. Tawangmangu tangerine (Citrus nobilis Lour. var Tawangmangu) is one of local high-quality oranges come from Tawangmangu area, Karanganyar District, Central Java, Indonesia. By adding orange juice powder in the process of making yogurt, it is expected to add flavor and increase the vitamin C content of yogurt, as well as increase the selling value of Tawangmangu tangerine. Inoculums used in this research were Lactobacillus bulgaricus, Streptococcus thermophilus, and Lactobacillus acidophilus. The results showed that the addition of Tawangmangu tangerine juice powder could increase the vitamin C content in yogurt. Highest vitamin C content was found on Tawangmangu tangerine juice powder 8% with a value of 6.23 mg/100g. Organoleptic test indicated that the addition of Tawangmangu tangerine juice powder increased panelists likeness for Tawangmangu tangerine yogurt, lowered level of fat and also increased the protein content in yogurt.